Right to government information: the importance of publishing and open access to official Colombian publications - Colmenares Moreno, Wilson Enrique (2023)
The lack of official publications awareness and the absence of editing processes can affect the right to open access to government information. This essay proposes the categories of editing and open access to official publications as fundamental processes to strengthen the right to government information in Colombia. It argues the importance of official publications as objects of documentary record, information representation, and bibliographic preservation necessary for understanding the purposes, facts, and consequences of governmental decisions and their effects on society. The field of study approached in this research was library science, employing a qualitative methodology with exploratory and descriptive scope. This essay identifies that at the international and national levels, there are studies and legislation that mention official publications; however, they lack a conceptualization that defines and describes their main characteristics according to each country's political system. Government information requires editing, publishing, legal deposit, and preservation processes in government libraries to enhance open access to official publications. Therefore, it becomes necessary to evaluate and identify the strengths and weaknesses of these processes for the formulation of public policies that define institutional responsibility, economic resources, and necessary infrastructure for fulfilling the right to government information in line with the dynamics of information technology and digital communication.